(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article is dedicated to the use of effective methods of movement games in the process of physical fitness activities on the educational agenda to increase the physical fitness of 7–8-year-old students in physical education classes and to plan movement games in fitness activities.